2019
DOI: 10.1186/s41038-019-0173-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigating clinical characteristics and prognostic factors in patients with chronic osteomyelitis of humerus

Abstract: BackgroundChronic osteomyelitis in the humerus, which has complex neuroanatomy and a good soft tissue envelope, represents a unique clinical challenge. However, there are relatively few related studies in the literature. This article retrospectively reviewed a large case series with the aims of sharing our management experiences and further determining factors associated with the outcomes.MethodsTwenty-eight consecutive adult patients with a mean age of 36 years were identified by reviewing the osteomyelitis d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Drilling in this location (as when employing intramedullary nailing for proximal two‐part humerus fractures) does not compromise humeral head blood flow 35 . Although this is an established method for debriding the medullary canal of the humerus and other long bones, 16,36 we felt that it would not have allowed for adequate debridement in our case (Figure 2).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Drilling in this location (as when employing intramedullary nailing for proximal two‐part humerus fractures) does not compromise humeral head blood flow 35 . Although this is an established method for debriding the medullary canal of the humerus and other long bones, 16,36 we felt that it would not have allowed for adequate debridement in our case (Figure 2).…”
Section: Discussionmentioning
confidence: 94%
“…Radiographs revealed a minimally displaced and mildly comminuted surgical neck fracture of the right humerus (Figure 1). Although examination of the radiographs revealed reduced bone density consistent with chronic alcoholism, 14 the admitting physicians and a radiologist concluded that the relatively obvious lytic changes that are typically seen in chronic osteomyelitis were not present 15,16 . After a 3‐day hospitalization that focused on correcting hyponatremia, she was discharged with the anticipation of nonoperative treatment.…”
Section: Case Presentationmentioning
confidence: 99%
“…Osteomyelitis involving humerus is rare clinical entity and management is derived from osteomyelitis involving tibia and femur, the overall incidence is 3.4% [ 8 ]. The patient presented with osteomyelitis secondary to local skin and soft-tissue infection which is less common than the post-traumatic forms presented in the literature [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has a broad antibacterial spectrum that covers most strains of bacteria, such as MRSA and methicillin-resistant S. epidermidis. Vancomycin bone cement plate has good therapeutic effects in the treatment of infected fractures, infected bone defects, fractures with osteomyelitis, infected nonunion, and various other diseases [88][89][90][91][92]. Compared with other commonly used antibiotics, such as gentamicin, vancomycin has a relatively lower toxic dose (1000 µg/mL) [93,94]; thus, coating vehicles with controlled vancomycin release are continually developed.…”
Section: Antibiotics As Coating Materialsmentioning
confidence: 99%